Farmer Community Empowerment Through Training on Making Simple Rice Husk Briquettes to Control Rice Rat Pest - Wahyuni, Hafnes; Hasibuan, Julia Syahriani; Ibrahim, R.B.Moh. (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2022)
Rats are one of the main pests of rice plants. The problem of rat pests is often a factor that can reduce agricultural production, especially rice plant. Kota Datar village, Hamparan Perak District, is one of the areas where rice is grown a lot. One alternative that can anticipate the problem of environmentally friendly field mice is to encourage farmers to make briquettes from rice husks. This service was carried out in August-October in the Kota Datar village, Hamparan Perak District, Deli Serdang Regency. The results obtained are to find a solution for controlling rice rat pests that are environmentally friendly by utilizing rice husk leftover from rice milling, namely making simple briquettes